REDESAIN KEMASAN MADU TRIGONA DAN KREASI KORAN BEKAS UNTUK RESTORASI EKONOMI UMKM BALI - Darmawan, Andreas James (Desain Komunikasi Visual, Manajemen Desain dan Periklanan (Demandia), 2023)
An effort and enthusiasm for the Balinese economy to revive after the pandemic, where the Ministry of Tourism and Creative Economy provided packaging design assistance for Micro, Small and Medium Enterprises (MSMEs) in Tenganan Village and Carangsari Village, Bali. The urgency of this research is to respond to the problem raised by the Visual Communication Design Study Program Association (Asprodi) which is improving packaging design in the 8th batch of Packaging Design Surgery (BEDAKAN) program. This research focuses on two MSME products; packaging design for Trigona Honey "Kele-Kele" and packaging design for Used Newspaper creations "Tirta Nadi". The method used is descriptive qualitative in nature, by collecting data based on direct discussions by representatives of the Ministry of Tourism and Creative Economy, Asprodi DKV, and the Association of Indonesian Industrial Product Designers (ADPII); offline and online interviews with related MSME entrepreneurs, followed by the process of making the initial stage of the packaging design, which eventually enters the packaging design finalization stage. This research resulted in a new packaging design for UMKM Madu Trigona "Kele-Kele" and the Creation of Used Newspapers "Tirta Nadi. Keywords: Packaging Design, Trigona Honey, Used Newspaper Creations